2018
DOI: 10.2135/cropsci2017.09.0530
|View full text |Cite
|
Sign up to set email alerts
|

Overseeding Cool‐Season Annual Legumes and Grasses into Dormant ‘Tifton 85’ Bermudagrass for Forage and Biomass

Abstract: Overseeding dormant bermudagrass [Cynodon dactylon (L.) Pers.] ‘Tifton 85’ with cool‐season annuals in the southeastern United States could provide winter and spring forage or bioenergy feedstock. We overseeded cool‐season annual legumes and grasses in monocultures or mixtures into dormant Tifton 85 and compared aboveground dry matter (DM) and N yields of single harvests at peak biomass production and a multiple harvest forage system. We also measured first‐cut spring Tifton 85 yields. Wheat (Triticum aestivum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…), and bermudagrass [ Cynodon dactylon (L.) Pers.] in the southeastern United States (Hoveland et al, 1978; Wyatt et al, 2012; White et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…), and bermudagrass [ Cynodon dactylon (L.) Pers.] in the southeastern United States (Hoveland et al, 1978; Wyatt et al, 2012; White et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…), and bermudagrass [Cynodon dactylon (L.) Pers.] in the southeastern United States (Hoveland et al, 1978;Wyatt et al, 2012;White et al, 2018). reported little effect of overseeding red clover into NWSG on forage mass, CP, neutral detergent fiber, or animal performance, likely due to low levels of clover after establishment.…”
Section: Herbage Accumulation and Nutritive Valuementioning
confidence: 99%
“…Overseeding cool-season forages can potentially increase animal performance during the cool season while optimizing land utilization and improving production throughout the year (Dubeux et al, 2016). White et al (2018) reported several options to optimize cool-season forage gains and subsequent early spring positive effects on forage production by overseeding bermudagrass [Cynodon dactylon (L.) Pers.]. Overseeding cool-season legumes on switchgrass (Panicum virgatum L.), also increased total biomass productivity (Mantino et al, 2020).…”
Section: Ta B L E a Useful Conversionsmentioning
confidence: 99%
“…Cool‐season annual legumes and grasses are commonly overseeded on warm‐season grass pastures, however results may vary from site to site (Han, Alison, Pitman, & McCormick, 2012; Mantino, Giannini, Tozzini, Bonari, & Ragaglini, 2020; White, Muir, & Lambert, 2018). Overseeding cool‐season forages can potentially increase animal performance during the cool season while optimizing land utilization and improving production throughout the year (Dubeux et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation